Analisiss Efektivitas dan Kontribusi Penerimaan Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) terhadap Pendapatan Asli Daerah (PAD) Kabupaten Tegal - Reny Gusandriani; Bahri Kamal; Fitri Amaliah (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
The existence of regional autonomy, the Regional Government is encouraged to find sources of regional income that can support regional expenditures. Effectiveness in realizing revenue must be achieved according to the target, because when this effectiveness is achieved, the goals desired by the agency will also be achieved properly. This study aims to determine the level of effectiveness of Land and Building Acquisition Fee (BPHTB) in Tegal Regency, and the contribution of Land and Building Acquisition Fee (BPHTB) to Original Regional Income (PAD) in Tegal Regency. The research method used is quantitative descriptive. The data collection methods used are observation, interviews, and documentation. The data used in this study are the target and realization of BPHTB revenues and the target realization of PAD revenues for 2019-2023. The results of this study indicate that the level of effectiveness of BPHTB revenues in Tegal Regency is classified as effective over the past 5 years because its realization has always been able to achieve the targets set by the government, while the level of contribution of BPHTB revenues to PAD in Tegal Regency has been very ineffective over the past 5 years. This is because PAD revenues do not only come from BPHTB taxes, but also from other regional tax revenues.